Plan de negocio para la creación y montaje de un centro de belleza en la ciudad de Santa Marta (2024)
The proposal consists of the creation of a beauty center in the city of Santa Marta, with the aim of offering high quality services in personal care and beauty. The beauty center will be located in a strategic commercial area, with easy access for clients and great visibility to attract new clients. Services offered include brushing, ironing, hair styling, makeup, pointto-point eyelashes, semi-permanent eyebrows, manicure, pedicure and minibar. There will be a highly trained and professional team, which will be available to clients to advise them and provide them with a personalized service. Additionally, high quality products will be used to ensure customer satisfaction. This document details the integrated recognition elements to denote and contextualize the proposal, using a qualitative methodology, all the steps for carrying out a structural business plan will be explained. A sector market study, a technical-operational study and finally an economic-financial investigation will be assessed.